The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5941/myco.2017.45.3.129
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Placement and Morphological Characterization of Sclerotium rolfsii (Teleomorph: Athelia rolfsii) Associated with Blight Disease of Ipomoea batatas in Korea

Abstract: In this study, we aimed to characterize fungal samples from necrotic lesions on collar regions observed in different sweetpotato growing regions during 2015 and 2016 in Korea. Sclerotia appeared on the root zone soil surface, and white dense mycelia were observed. At the later stages of infection, mother roots quickly rotted, and large areas of the plants were destroyed. The disease occurrence was monitored at 45 and 84 farms, and 11.8% and 6.8% of the land areas were found to be infected in 2015 and 2016, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…It causes the disease known as sclerotium rot or sclerotium wilt, widely distributed in tropical and subtropical regions (Punja and Damiani, 1996;Mahadevakumar et al, 2016). S rolfsii is known to infect several economically important crops in various stages of their growth and development, in addition to producing survival structures (Mahadevakumar et al, 2016;Paul et al, 2017;Shrestha et al, 2018). Studies conducted in Sri Lanka (Jegathambiga et al, 2010) reported the occurrence of rot symptoms in Zamioculcas sp.…”
Section: Pathogenecity Testmentioning
confidence: 99%
“…It causes the disease known as sclerotium rot or sclerotium wilt, widely distributed in tropical and subtropical regions (Punja and Damiani, 1996;Mahadevakumar et al, 2016). S rolfsii is known to infect several economically important crops in various stages of their growth and development, in addition to producing survival structures (Mahadevakumar et al, 2016;Paul et al, 2017;Shrestha et al, 2018). Studies conducted in Sri Lanka (Jegathambiga et al, 2010) reported the occurrence of rot symptoms in Zamioculcas sp.…”
Section: Pathogenecity Testmentioning
confidence: 99%
“…Sclerotium rolfsii is an important stem and root rot pathogen of many crops (Talukder et al, 2019). This fungus is a highly polyphagous pathogen, and due to its wide host range, it is considered one of the most destructive Damping-off in Vigna subterranea and identification of associated causal agents pathogens in the world (Paul et al, 2017). The pathogen attacks around 500 plant species from 100 different botanical families (Punja, 1985;Blancard, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogen attacks around 500 plant species from 100 different botanical families (Punja, 1985;Blancard, 1988). Among its cultivated host plants are tomato (Sikirou et al, 2011), potato, cassava, chili, carrot, cabbage, peanut (Dwivedi andPrasad, 2016), cowpea (Adandonon et al, 2015), sweet potato (Paul et al, 2017), coffee, oil palm (Okabe and Matsumoto, 2000), Bambara groundnut and fruit plants (banana, citrus) (Ayandoo et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of stem rot disease in legume plants include initially drooping of leaves close to the ground, while the branches become wilted and yellowish. Furthermore, the leaves slowly turn dark brown and sometimes fall from the plants prematurely, while the branches wither and also turn dark brown, and the lower trunk adjacent to the ground is covered with white mycelium and sclerotia growth (Karthikeyan et al, 2015;Paul et al, 2017;Nugroho et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A. rolfsii produces an extracellular enzyme, namely cellobiose dehydrogenase (CDH) used to penetrate the host plant, while S. rolfsii also produce six extracellular enzymes, including amylase, carboxymethyl cellulase, lipase, laccase, catalase and gelatinase which are used to infect plant tissues (Chaurasia et al, 2015;Elias et al, 2015;Sennoi et al, 2021). The macroscopic and microscopic morphology of the two species are the same and difficult to distinguish, hence, molecular identification is needed to differentiate between the species (Paul et al, 2017).…”
Section: Introductionmentioning
confidence: 99%